Exploring Ulex europaeus to Produce Nontoxic Binderless Fibreboard - Hector Pesenti; Marco Torres; Patricia Oliveira; Willian Gacitua; Matteo Leoni (BioResources, 2017)
Ulex europaeus is one of the most abundant and aggressively invasive plants on the world. Its fibres, which can be isolated using an alkaline pulping process, have been successfully thermo-pressed into high-density fibreboards without any type of binder. The influence of the bioorganic and crystalline components on the product was investigated using crystallographic, thermo-analytical, and mechanical techniques. Cellulose was predominantly an Iβ polymorph, more common in hardwood, but the composition of the material was typical of softwood. Both the crystallinity in the fibres and the average domain size of cellulose increased during thermo-pressing. Notwithstanding that the residual lignin was present in a small amount, this promoted the cohesion of fibres by improving hydrolysis and adhesion properties. The best overall properties were observed in the pressed products of 1030 ± 38 kg/m3, showing an elastic modulus of 4.31 ± 0.26 GPa, with a modulus of rupture of 26.5 ± 1.3 MPa. These results serve as the basis to transform the invasive species into a fully non-toxic added-value resource.